Modeling and Optimizing of Producing Recycled PET from Fabrics Waste via Falling Film-Rotating Disk Combined Reactor - Dan Qin; Chaosheng Wang; Huaping Wang; Ye Chen; Peng Ji; Zhenhao Xi (International Journal of Polymer Science)
Recycling and reusing of poly (ethylene terephthalate) (PET) fabrics waste are essential for reducing serious waste of resources and environmental pollution caused by low utilization rate. The liquid-phase polymerization method has advantages of short process flow, low energy consumption, and low production cost. However, unlike prepolymer, the material characteristics of PET fabrics waste (complex composition, high intrinsic viscosity, and large quality fluctuations) make its recycling a technique challenge. In this study, the falling film-rotating disk combined reactor is proposed, and the continuous liquid-phase polymerization is modeled by optimizing and correcting existing models for the final stage of PET polymerization to improve the product quality in plant production. Through modeling and simulation, the weight analysis of indexes closely related to the product quality (intrinsic viscosity, carboxyl end group concentration, and diethylene glycol content) was investigated to optimize the production process in order to obtain the desired polymer properties and meet specific product material characteristics. The model could be applied to other PET wastes (e.g., bottles and films) and extended to investigate different aspects of the recycling process.